Public Money The Systems Solution to End National Debt, Banking Crisis, Built-In Inequality, Inflation and Control by CBDC - Yamaguchi, Kaoru; Yamaguchi, Yokei (Springer Nature Singapore : Imprint: Springer, 2024)
XXI, 451 p. 111 illus., 107 illus. in color.